2022
DOI: 10.1093/ofid/ofac608
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Syndrome Imitating Cutaneous Cryptococcal Disease

Abstract: Cryptococcoid Sweet syndrome is a rare histologic variant of the neutrophilic dermatosis presenting clinically with skin lesions typical of classical Sweet syndrome but with yeast-like structures suggestive of Cryptococcus on histopathology. Histochemical stains for fungus and cultures are negative while staining for myeloperoxidase is positive. We present two cases of cryptococcoid Sweet syndrome with atypical skin manifestations, including hemorrhagic bullae and plaques, and provide a brief review of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Table 1 outlines the clinical, laboratory, and histopathologic findings as well as the treatment course for these cases. [1][2][3][4][5][6][7][8][9] From this collated data, the average age of presentation was 71 years and there was a female predominance (75%). Clinical features were similar among cases and mirrored those associated with classic Sweet syndromenamely, the acute onset of tender, sharply demarcated, edematous, erythematous to violaceous papules, plaques, and nodules favoring the head, neck, and upper extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 outlines the clinical, laboratory, and histopathologic findings as well as the treatment course for these cases. [1][2][3][4][5][6][7][8][9] From this collated data, the average age of presentation was 71 years and there was a female predominance (75%). Clinical features were similar among cases and mirrored those associated with classic Sweet syndromenamely, the acute onset of tender, sharply demarcated, edematous, erythematous to violaceous papules, plaques, and nodules favoring the head, neck, and upper extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Since this time, seven additional cases have been reported, plus this case for a total of 16 cases to date. Table 1 outlines the clinical, laboratory, and histopathologic findings as well as the treatment course for these cases 1–9 . From this collated data, the average age of presentation was 71 years and there was a female predominance (75%).…”
Section: Discussionmentioning
confidence: 99%
“…A series of case reports showed that five out of eight patients with giant cellulitis-like SS were correlated with various malignancies such as myeloma, breast carcinoma, and acute myeloid leukemia (AML) [ 4 , 5 ]. A rare histologic variant of the crypto-coccoid Sweet syndrome can present with atypical hemorrhagic bullae and yeast-like structures imitating cutaneous cryptococcal disease [ 6 ]. The histological finding of a dense neutrophilic infiltrate without leukocytoclastic vasculitis supports the diagnosis of SS, therefore skin biopsy should be performed whenever feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions predominantly occur on the head, neck, and limbs, and have various clinical features, including acneiform papules, violaceous plaques, nodules, blisters, and ulcers . In addition to the clinical resemblance between Sweet syndrome and cutaneous cryptococcosis, the histologic findings of dermal infiltration of myeloperoxidase-positive myeloid cells with a surrounding halo, which are morphologically suggestive of cryptococcal organisms, have been described in cases of neutrophilic Sweet syndrome and HSS (cryptococcoid Sweet syndrome) . Cryptococcus in biopsy specimens can be identified as fungal elements surrounded by a bright area (a polysaccharide capsule) with hematoxylin-eosin staining.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition to the clinical resemblance between Sweet syndrome and cutaneous cryptococcosis, the histologic findings of dermal infiltration of myeloperoxidase-positive myeloid cells with a surrounding halo, which are morphologically suggestive of cryptococcal organisms, have been described in cases of neutrophilic Sweet syndrome and HSS (cryptococcoid Sweet syndrome). 10 Cryptococcus in biopsy specimens can be identified as fungal elements surrounded by a bright area (a polysaccharide capsule) with hematoxylin-eosin staining. Pathogens are stained by periodic acid-Schiff stain and Grocott methenamine silver stain, and their capsules are stained by mucicarmine.…”
Section: Discussionmentioning
confidence: 99%